THE SPEECH ACTS OF BANTENESE FAMILY IN MEDAN JOHOR - Fernando De Napoli Marpaung (LPPM STKIP AL MAKSUM, 2019)
This research focuses on the types of speech acts and the meaning of the utterances used by Bantenese family. The study aims to find out the types of speech acts, the dominant type of speech acts used by Bantenese family in Medan Johor and the interpretation of the reason of Bantenese use these types of speech acts in their dialogues. This thesis conducts on the descriptive qualitative method. Descriptive design simply describes what data shows. This research elaborates on the utterances assumed to contain illocutionary acts. The findings of the research show the speech acts that occurred on Bantenese family in Medan Johor are assertive, directive, expressive, commissive and declarative. The presentations are: assertives acts 27.5%, directives acts 58.75%, commissives acts 5%, expressives acts 7.5%, and declaratives acts 1.25%. If elaborated, there are several dialogues in Bantenese family. There are between parents to children, children to parents, between sisters and brothers, husband and wife, grandmother to grandchildren and the last between aunt to nephew. The writer also finds that Bantenese usually or often used the statement in command, request, advice, offering, suggesting, confirmation, boasting, resigning and expressing something. It is shown from pragmatic meaning that is utterenced by Bantenese. In daily communication or dialogue in Bantenese family, they often say 'A' but the meaning is 'B' . They say with the statement that has meaning something.